Discovery of KDM5D as a novel biomarker for traumatic brain injury identified through bioinformatics analysis - Ding, Dengfeng; Yang, Mengzhe; Zheng, Xinou; Zhao, Ming (Frontiers in Immunology, 2025)
Background and aimTraumatic brain injury (TBI) poses a significant burden on the global economy due to its poor treatment and prognosis. Current TBI markers do not comprehensively reflect the disease status. Therefore, identifying more meaningful biomarkers is beneficial for improving the prognosis and clinical treatment of TBI patients.MethodsThe gene expression profile of TBI was obtained from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) were subjected to enrichment analysis, and key potential genes were identified through the protein–protein interaction network and cytoHubba modules. ROC curves were used to construct diagnostic models for hub genes. Immunofluorescence experiments were conducted to detect the expression of candidate biomarkers in TBI rat models. Finally, we investigated the expression of TBI biomarkers in normal human organs and pan-cancer tumor tissues, and evaluated their correlation with immune infiltration in different tumors.ResultsA total of 44 DEGs were identified across four brain regions of TBI patients. Enrichment analysis revealed that these genes were primarily involved in intracellular and cell signal transduction pathways. Furthermore, three hub genes- RPS4Y1, KDM5D and NLGN4Y-were identified through different module analysis. The ROC curve diagnostic model also confirmed that these genes also have high diagnostic value in serum. Subsequently, the presence of Kdm5d was detected in the brain tissue of TBI rats through immunofluorescence experiments. Compared to normal rats, Kdm5d expression increased in the cortical area of ​​TBI rats, with no significant change in the hippocampus area, aligning with observations in TBI patients. Immune infiltration analysis demonstrated changes in immune cell subsets in HIP and PCx, revealing that plasma cells and CD8 T cells were lowly expressed in TBI (HIP) and while neutrophils was under-expressed in TBI (PCx). Pan-cancer analysis indicated that KDM5D was significantly up-regulated in 23 cancers, down-regulated in 3 cancers, and significantly associated with immune infiltration in 10 cancers.ConclusionBased on the results of bioinformatics analysis and animal experiments, KDM5D serves as a potential biomarker for the diagnosis and prognosis of TBI. Additionally, research on KDM5D may develop into new serum markers, providing new indicators for further clinical liquid biopsy and aiding in the prevention of both TBI and tumors to a certain extent.